Examining the performance of Shari’ah‑compliant versus conventional stock indexes: A comparative analysis pre-, during, and post-COVID-19 - Abu-Alkheil, Ahmad; Alsharari, Nizar; Khan, Walayet; Ramzani, Sara; Horam, Phungmayo (Economics and Business Review, 2024)
This study aims to conduct an empirical comparative analysis of the performance of Shari’ah and conventional stock indexes during the period 2017–2023, which includes the COVID-19 pandemic. Additionally, it aims to investigate investors’ preferences and analyse the long-term relationship of these indexes, as well as exploring the potential diversification benefits. The research methodology incorporates stochastic dominance analysis, the VARMAX procedure, and Johansen’s co-integration approach. The data utilized consists of 31 conventional and 31 Islamic stock indexes, specifically from the FTSE, DJ, MSCI, and S&P series.The results show that there are no long-term co-integration links between 30 out of 31 pairs of Islamic and conventional indexes. While conventional indexes tend to outperform Islamic indexes, they also come with a higher risk. On the other hand, Islamic indexes are considered to be less risky, offering potential diversification opportunities that may be attractive for global portfolios, particularly during periods of financial distress.